The Influence of Job Satisfaction on Employee Performance through Work Motivation with Moderation of Leadership Style at CV. Union Event Planner - Yanti, Ni Putu Desi; Suryawati, Ni Made Rai (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
This study aims to analyze the effect of job satisfaction and work motivation on employee Performance at CV Union Event Planner by considering the role of leadership style as a supporting variable. Employee Performance is understood as the real contribution of individuals in achieving organizational goals, which are influenced by intrinsic and extrinsic factors. Using a quantitative approach with a census method on 57 employees, data were collected through questionnaires and analyzed using descriptive statistical techniques and multiple linear regression. The results showed that job satisfaction and work motivation have a positive effect on employee Performance. The classical assumption test showed that the regression model was free from multicollinearity and heteroscedasticity. The leadership style variable also showed quite high variation, indicating the importance of attention to leadership in the organization. These findings emphasize the importance of a comprehensive human resource management strategy, with an emphasis on developing motivation, job satisfaction, and leadership as the key to increasing the company's competitiveness.